Chemiluminescent polymeric nanoprobes for tumor diagnosis: A mini review - Zhang, Xiaoyan; Li, Cong; Chen, Wenjuan; Wang, Guanhua; Zou, Huiru; Liu, Hao (Frontiers in Chemistry, 2023)
Chemiluminescence (CL), a distinct luminescent process by taking advantage of chemical reactions rather than external light source, has recently attracted considerable research interests due to its high sensitivity and low background signal. The sensitivity and specificity of chemiluminescent signals in complex tumor microenvironment provide a sound basis for accurate detection of tumors. Various chemiluminescent nanoprobes with superior performance have been obtained by structural modification of chemiluminescent units or introduction of fluorescent dyes. In this review, we focused on the recent progress of chemiluminescent polymeric systems based on various chromophore substrates, including luminol, peroxyoxalates, 1, 2-dioxetanes and their derivatives for tumor detecting. And we also emphasized the design strategies, mechanisms and diagnostic applications of representative chemiluminescent polymeric nanoprobes. Finally, the critical challenges and perspectives of chemiluminescent systems usage in tumor diagnosis were also discussed.